Increasing Slow Learner Reading Abilities Through Functional Reading : A Single-Case Study on An Elementary School Student - Shinta Nauli, Michelle Torita; Royanto, Lucia RM (Jurnal Paedagogy, 2024)
This study explored the effectiveness of teaching functional literacy to a 12-year-old slow learner in Indonesia. The participant struggles read words longer than two syllables and struggles to meet academic expectations. This research uses a qualitative approach with the single-subject design using the reversal method or the ABA research design.  Data was collected through three phases: baseline, intervention, and evaluation phases. This study utilizes two sets of flashcards as instruments. The first set consists of pictorial cards displaying twelve common street signs, while the second set contains word cards with the matching names of the signs in Bahasa Indonesia. Each card is printed on a 13 cm by 7 cm flashcard. Over the intervention sessions, the participant demonstrated significant progress in functional reading skills. The data collected was then analyzed using visual analysis. The results indicates that slow learners benefit from frequent, concrete, and visually based learning abilities that aligns for their need for repetition. This study highlights the importance of functional literacy in enhancing independent living skills among slow learners, providing the students with the tool to better navigate their surroundings.